2022
DOI: 10.3389/fsurg.2022.950108
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of Ivor Lewis vs. McKeown esophagectomy: A meta-analysis

Abstract: ObjectiveThe objective of this article is to assess the rate of anastomotic leak and other perioperative outcomes in patients undergoing esophagectomy with either thoracic or cervical anastomosis.MethodsThis meta-analysis was conducted by searching relevant literature studies in Web of Science, Cochrane Library, PubMed, and Embase databases. Articles that included patients undergoing esophagectomy and compared perioperative outcomes of McKeown with Ivor Lewis procedures were included. The primary outcome param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…21 The McKeown procedure has the advantages of cervical lymph node dissection and more proximal resection margins in terms of oncologic efficacy; however, no difference was observed in the total lymph nodes retrieved during surgery and R0 resection rates between the two procedures in the meta-analysis. 43 These results…”
Section: Comparison Of Ivor Le Wis and M Ck Eown Pro Cedurementioning
confidence: 71%
See 4 more Smart Citations
“…21 The McKeown procedure has the advantages of cervical lymph node dissection and more proximal resection margins in terms of oncologic efficacy; however, no difference was observed in the total lymph nodes retrieved during surgery and R0 resection rates between the two procedures in the meta-analysis. 43 These results…”
Section: Comparison Of Ivor Le Wis and M Ck Eown Pro Cedurementioning
confidence: 71%
“…46 Further, the meta-analysis reported that the McKeown procedure was associated with significantly higher grades of anastomotic leakage and recurrent laryngeal nerve palsy than the Ivor Lewis procedure. 43 Therefore, the anastomotic leakage rate was higher in the McKeown procedure; however, the RCT reported that the anastomotic leakage rate in the McKeown procedure was 34.1%, 43 which was considerably higher than that reported in NCD data in Japan. 21 The McKeown procedure has the advantages of cervical lymph node dissection and more proximal resection margins in terms of oncologic efficacy; however, no difference was observed in the total lymph nodes retrieved during surgery and R0 resection rates between the two procedures in the meta-analysis.…”
Section: Comparison Of Ivor Le Wis and M Ck Eown Pro Cedurementioning
confidence: 89%
See 3 more Smart Citations